Evaluation of temperature-pulse centile charts in identifying serious bacterial illness: Observational cohort study - Brent, A; Lakhanpaul, M; Ninis, N; Levin, M; MacFaul, R; Thompson, M (2011)
Background: Distinguishing serious bacterial infection (SBI) from milder/self-limiting infections is often difficult. Interpretation of vital signs is confounded by the effect of temperature on pulse and respiratory rate. Temperature-pulse centile charts have been proposed to improve the predictive value of pulse rate in the clinical assessment of children with suspected SBI. Objectives: To assess the utility of proposed temperature-pulse centile charts in the clinical assessment of children with suspected SBI. Study design and participants: The predictive value for SBI of temperature-pulse centile categories, pulse centile categories and Advanced Paediatric Life Support (APLS) defined tachycardia were compared among 1360 children aged 3 months to 10 years presenting with suspected infection to a hospital emergency department (ED) in England; and among 325 children who presented to hospitals in the UK with meningococcal disease. Main outcome measure: SBI. Results: Among children presenting to the ED, 55 (4.0%) had SBI. Pulse centile category, but not temperature-pulse centile category, was strongly associated with risk of SBI (p=0.0005 and 0.288, respectively). APLS defined tachycardia was also strongly associated with SBI (OR 2.90 (95% CI 1.60 to 5.26), p=0.0002). Among children with meningococcal disease, higher pulse and temperature-pulse centile categories were both associated with more severe disease (p=0.004 and 0.041, respectively). Conclusions: Increased pulse rate is an important predictor of SBI, supporting National Institute for Health and Clinical Excellence recommendations that pulse rate be routinely measured in the assessment of febrile children. Temperature-pulse centile charts performed more poorly than pulse alone in this study. Further studies are required to evaluate their utility in monitoring the clinical progress of sick children over time.